Mutation enrichment in human DNA samples via UV-mediated cross-linking. Issue 6 (14th December 2021) - Leong, Ka Wai; Yu, Fangyan; Makrigiorgos, G Mike
Abstract: Detection of low-level DNA mutations can reveal recurrent, hotspot genetic changes of clinical relevance to cancer, prenatal diagnostics, organ transplantation or infectious diseases. However, the high excess of wild-type (WT) alleles, which are concurrently present, often hinders identification of salient genetic changes. Here, we introduce U V-mediated c ross-linking minor allele e nrichment (UVME), a novel approach that incorporates ultraviolet irradiation (∼365 nm UV) DNA cross-linking either before or during PCR amplification. Oligonucleotide probes matching the WT target sequence and incorporating a UV-sensitive 3-cyanovinylcarbazole nucleoside modification are employed for cross-linking WT DNA. Mismatches formed with mutated alleles reduce DNA binding and UV-mediated cross-linking and favor mutated DNA amplification. UV can be applied before PCR and/or at any stage during PCR to selectively block WT DNA amplification and enable identification of traces of mutated alleles. This enables a single-tube PCR reaction directly from genomic DNA combining optimal pre-amplification of mutated alleles, which then switches to UV-mediated mutation enrichment-based DNA target amplification. UVME cross-linking enables enrichment of mutated KRAS and p53 alleles, which can be screened directly via Sanger sequencing, high-resolution melting, TaqMan genotyping or digital PCR, resulting in the detection of mutation allelic frequencies of 0.001–0.1% depending on the endpoint detection method. UV-mediated mutation enrichment provides new potential for mutation enrichment in diverse clinical samples.